2018
DOI: 10.1108/ijge-07-2017-0032
|View full text |Cite
|
Sign up to set email alerts
|

Female business owners hiding in plain sight

Abstract: Purpose-The purpose of this paper is to explore what female business owners hide to better understand social norms and discourses that influence the decisions women make about how they structure their home and work lives. Design/methodology/approach-The author used qualitative interviews to access the narratives of female business owners in public relations within the USA. This industry segment attracts primarily women and, unlike a retail store, offers women a variety of ways to structure their business hours… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
(85 reference statements)
0
4
0
Order By: Relevance
“…Meanwhile, the entrepreneurship literature has neglected various influences of gender on entrepreneurs' decisions, including decision-making biases (Shepherd et al, 2015). Given the increasing importance of women entrepreneurs (Hughes et al, 2012), the unique set of challenges women entrepreneurs encounter isn't their business activities (Weidhaas, 2018), as well as the vital managerial implications of biases, especially escalation of commitment (Bazerman and Moore, 2013), the lack of research on women entrepreneurs' biases may be very disadvantageous for them. Thus, by exploring the antecedents of escalation of commitment in women entrepreneurs, this paper enhances two crucial areas of women entrepreneurship as well as entrepreneurial decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the entrepreneurship literature has neglected various influences of gender on entrepreneurs' decisions, including decision-making biases (Shepherd et al, 2015). Given the increasing importance of women entrepreneurs (Hughes et al, 2012), the unique set of challenges women entrepreneurs encounter isn't their business activities (Weidhaas, 2018), as well as the vital managerial implications of biases, especially escalation of commitment (Bazerman and Moore, 2013), the lack of research on women entrepreneurs' biases may be very disadvantageous for them. Thus, by exploring the antecedents of escalation of commitment in women entrepreneurs, this paper enhances two crucial areas of women entrepreneurship as well as entrepreneurial decision-making.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, given the growing importance of women's entrepreneurship (Hughes et al. , 2012), the operational implications of biases for entrepreneurs (Cossette, 2014), especially for women entrepreneurs who encounter a unique set of challenges in their business activities (Weidhaas, 2018), this lack of proper studies has created an important research gap in the field of women entrepreneurship. This shortcoming is more underlined concerning women entrepreneurs in developing countries like Iran, who encounter various impediments in their entrepreneurial activities (Nouri, 2021b).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Difference in Work Experience in the Same Industry between MNV and FNV owners and its impact on New Venture Performance Work experience in the same industry is an important form of human capital (Becker, 1964). Numerous studies have shown that human capital of the founders by virtue of the work experience in a similar industry is positively correlated with the starting and the performance of a new venture (Colombo and Grilli, 2005;Cooper et al, 1994;Dahl and Reichstein, 2007;Weidhaas, 2018;Xu, 2019). Founders who have worked in an industry in which they start a venture can leverage contacts with buyers, suppliers, and other stakeholders to operate their enterprise cost-efficiently.…”
Section: Gender and New Venture Performancementioning
confidence: 99%